Edge restricted detour index of some graphs. (18th May 2020) - Abdullah, Herish O.; Omar, Zhian I.
Abstract: The edge restricted detour distance D *0 ( f, g ) between two edges f and g of a connected graph G is equal to the restricted detour distance D *( f, g )* between vertices f and g in the line graph of G .